Image of Motivation in Hemodialized Patients with Low Self-Esteem - Rizka Ausrianti; Rifka Putri Andayani (Jurnal Ilmu Keperawatan Jiwa, 2021)
Hemodialysis is a treatment program that must be carried out life in patients with cronick kidney disease. This can cause various problems physically, socially and psychologically, including low self-esteem psychosocial problems and ultimately have an impact on motivation. This study aims to determine the description of motivation in hemodialysis patient with low self-esteem.  The reseach method used is descriptive with a cross sectional approach.The Samplinh technique used total sampling with a ample size of 43 hemodialisys patients with self-esteem in the city Padang. The result showed that the patient's motivation showed low motivation for hemodialysis patients with low self-esteem at the hospital in the city of Padang. Suggestions need a nursing intervention to increase the self- seteem of hemodialysis patients who  experience low self-esteem.